(untitled) - Lowman, Paul D. (Cambridge, 2002)
This book describes the impact of space flight on geology and geophysics, beginning with a foreword by Neil Armstrong, which illustrates how the exploration of space has lead us to a far deeper understanding of own planet. Direct results from Earth-orbital missions include studies of Earth's gravity and magnetic fields. In contrast, the recognition of the economic and biological significance of impact craters on Earth is an indirect consequence of the study of the geology of other planets
Keywords: Earth sciences,Astronautics in earth sciences,Khoa học trái đất,Ngành du hành vũ trụ trong khoa học trái đất; Remote sensing,Viễn thám